2008
DOI: 10.1017/s1742170507002062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling carbon cycles and estimation of greenhouse gas emissions from organic and conventional farming systems

Abstract: The paper describes the model software REPRO (REPROduction of soil fertility) designed for analyzing interlinked carbon (C) and nitrogen (N) fluxes in the system soil–plant–animal–environment. The model couples the balancing of C, N and energy fluxes with the target to estimate the climate-relevant CO2, CH4 and N2O sources and sinks of farming systems. For the determination of the net greenhouse effect, calculations of C sequestration in the soil, CO2 emissions from the use of fossil energy, CH4 emissions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 33 publications
2
56
0
1
Order By: Relevance
“…The results indicate that GHG emissions from conventional and organic agriculture are relatively equivalent for fuel consumption and machinery use (Küstermann et al, 2007). The study revealed that the major defining difference is conventional farming produces an additional 637 kg CO 2 -eq ha −1 yr −1 of GHG emissions, which is primarily caused by the manufacturing of nitrogen fertilizer and pesticides (Küstermann et al, 2007).…”
Section: Role In Reducing Greenhouse Gas Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that GHG emissions from conventional and organic agriculture are relatively equivalent for fuel consumption and machinery use (Küstermann et al, 2007). The study revealed that the major defining difference is conventional farming produces an additional 637 kg CO 2 -eq ha −1 yr −1 of GHG emissions, which is primarily caused by the manufacturing of nitrogen fertilizer and pesticides (Küstermann et al, 2007).…”
Section: Role In Reducing Greenhouse Gas Emissionsmentioning
confidence: 99%
“…A separate study in the Federal Republic of Germany tested GHG emissions on 90 farms with the aim to improve the field of research and the management of commercial farms (Küstermann et al, 2007). The results indicate that GHG emissions from conventional and organic agriculture are relatively equivalent for fuel consumption and machinery use (Küstermann et al, 2007).…”
Section: Role In Reducing Greenhouse Gas Emissionsmentioning
confidence: 99%
“…[12] includes the addition of organic waste among the management practices related to carbon sequestration. [13,14] have observed that organic agriculture systems (no synthetic fertilisers) produce less greenhouse gas than traditional systems.…”
Section: Organic Biowastementioning
confidence: 99%
“…But the human activities have altered the chemical composition of the atmosphere through the buildup of greenhouse gasesprimarily carbon dioxide, methane, and nitrous oxide. Bjorn [1] has published paper on Modeling carbon cycles and estimation of greenhouse gas emissions from organic and conventional farming systems. It gives information on carbon (C) and nitrogen (N) fluxes in the system soil-plant-animal-environment [2] .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%